2020
DOI: 10.1787/f16c7ae5-en
|View full text |Cite
|
Sign up to set email alerts
|

Attendance in early childhood education and care programmes and academic proficiencies at age 15

Abstract: Unclassified OECD EDUCATION WORKING PAPERS SERIES OECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed herein are those of the author(s). Working Papers describe preliminary results or research in progress by the author(s) and are published to stimulate discussion on a broad range of issues on which the OECD works. Comments on Working Papers are welcome, and may be sent to the Directorate for Educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(33 reference statements)
0
1
0
1
Order By: Relevance
“…Interestingly, a recent working paper released by OECD based on the PISA database (Balladares & Kankaraš, 2020) verified the existence of a relationship between students' ECEC (Early Childhood Education and Care) attendance and their later academic proficiency using PISA 2015 data. The result showed that SES played an important role, as there was a significant association between children's SES and the age of entry in ECEC.…”
Section: Contextual Parental Education and Growth In Emergent Literac...mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent working paper released by OECD based on the PISA database (Balladares & Kankaraš, 2020) verified the existence of a relationship between students' ECEC (Early Childhood Education and Care) attendance and their later academic proficiency using PISA 2015 data. The result showed that SES played an important role, as there was a significant association between children's SES and the age of entry in ECEC.…”
Section: Contextual Parental Education and Growth In Emergent Literac...mentioning
confidence: 99%
“…Curiosamente, un reciente documento de trabajo, publicado por la OCDE, basado en el informe PISA (Balladares & Kankaraš, 2020) corroboró la existencia de una relación entre la asistencia a un centro de educación y cuidado durante la primera infancia (ECEC, por sus siglas inglesas) y el rendimiento académico posterior, utilizando datos del informe PISA de 2015. Los resultados mostraron que el NSE desempeña un papel importante, dada la existencia de una relación significativa entre el NSE de los alumnos y la edad de ingreso en un centro ECEC.…”
Section: Educación Parental Contextual Y Desarrollo De Las Habilidade...unclassified